Strategy of local treatment in prostate cancer - Senkus-Konefka, Elżbieta; Jassem, Jacek (Contemporary Oncology/Współczesna Onkologia, 2003)
Prostate cancer is one of the most common malignancies in men. Over the last years, there has been a significant increase in the number of early cases, mainly due to the widespread use of PSA screening and the increasing mean age of the population. Main treatment modalities in early prostate cancer include surgery and radiotherapy. In patients with very low risk of progression and in those who are not suitable for radical local treatment, watchful waiting remains a viable option. Local methods can be combined (in various sequences) with hormonal therapy. Despite many years of research and numerous comparative studies, no definitive evidence is available to support the superiority of any of the treatment strategies and no unequivocal management algorithms exist for particular patient subgroups. The choice of treatment is additionally clouded by long and often unpredictable disease course. Furthermore, numerous co-morbidities typical for elderly population often render radical treatment impossible. As elderly patients often die with, but not because of prostate cancer, issues needed to be considered in treatment decision-making, apart from therapeutic effect, should include the risk of complications and quality of life. This article reviews contemporary literature on an optimal strategy of local treatment in non-metastatic prostate cancer patients.